Experience, art and education from Dewey's analytical perspective (Revista Apotheke, 2023)
The text consists of seven parts starting from an introduction in which the bibliographical proposal is presented, basically developing through John Dewey's references that deal with the theme involving art and education, based on the concept of experience. After exposing some theoretical and biographical information about the author, we start with the problem of dualisms present in our culture, since the Greeks, which led to a disregard of experience in favor of the dimension of theory, privileged locus of truth. In this sense, art being in the context of human practice, it developed in empiricism, locating itself in a dimension of inferiority compared to the noble activities of the spirit, whose contemplation was understood as the source of true scientific knowledge. This understanding of human knowledge generated difficulties that are still observed in a markedly elitist and prejudiced unfair classification. Such prejudices demand urgent formative work from education so that Dewey's prophecy does not come true, according to which, if workers do not appropriate the fundamentals of their activities, they will easily become mere appendages of technology and the machines that operate. Intending to make the philosophy of education essentially accessible and closely linked to pedagogical practices, Dewey starts from the experience vitally associated with human and social development, as long as it presents an aesthetic quality that makes it unique and is a guarantee of procedural, constant and truly educational growth. We realize the importance of art in education alongside science and philosophy, for the improvement of increasingly advanced thinking to face the problems present in the world of experiences.
Keywords: education; art; experience; Dewey